Pemanfaatan Ekstrak Etanol Daun Murbai (Morus alba L.) Sebagai Bahan Aktif Pasta Gigi Dan Uji Aktivitas Anti Bakteri Terhadap Plak Gigi - Akmal Djamaan; Fatimah Saidah; Rina Wahyuni (Jurnal Farmasi Higea, 2014)
The formulation of leaf´s murbey ethanol extract´s toothpaste and its activities against dental plaque´s bacteries had been done. Pre test showed the leaf´s murbey ethanol extracts at 4% of concentration gave an optimal diameter of inhibition against dental plague. Based that fact, this research would have made 3 formulas at toothpaste from leaf´s murbey extract at 1%, 2%, and 4% of concentration. All of formulas would have wade with the same base of toothpaste. All of formulas would be characterized of pharmaceutic´s properties and antibacteria´s activities, that would be compared with toothpaste “S” and “P” as a standard. The result shawed all formulas gave a good characteristic of pharmaceutic properties. F3 had gave a good diameter of inhibition, that was 21.875 mm, where as the “S” and “P” of toothpaste had gave a diameter of inhibition respectively 23.875 mm and 22.75mm. There was a significant difference of inhibition´s diameter of all formulas at 0.05 level of confidence.